Het barbertje : het zangboekje van de JNM. - Jeugdbond voor Natuurstudie en Milieubescherming (JNM) (Gent : JNM.)
Deze publicatie bevat volgende liederen
Aicha
Annabel
Angie
Anne
Alabama song
Aline
All shock up
Always look on the bright side of life
Baby one more time
Basket Case
Beautiful day
Boy's don't cry
Breakfast at Tiffany's
Californication
Brown eyed girl
Chan Chan
Clandestino
Cockles and mussles
Copacabana
Dans les yeux de ma mère
De aarde
Creep
De fanfare van honger en dorst
De rode man blues
De zottemorgen
De wereld is om zeep
Demasiado corazon
Den eglantier
Die laughing
Don't worry, be happy
Dromen zijn bedrog
Gimme hope Johanna
Graceland
Hallelujah
Eenzaam zonder jou
Hard times
Heart of gold
Het is een nacht
Hey, hey, my, my
I shot the sheriff
Hurricane
I hope that I don't fall in love with you
I'm gonna be
I can see clearly now
Instant street
Jimmy de eenzame fietser
I want you
Ik voel me zo verdomd alleen
Jailhouse rock
Ik hou van u
Je suis venu te dire que je m'en vais
Julie
Knocking on Heaven's door
Jolene
Kom van dat dak af
La vallée sacrée
La bamba
Kryptonite
Laat ons een bloem
Le vent nous portera
Layla
Lentelied
Lemon tree
Liefde voor muziek
Lieve kleine piranha
Lieve loemoemba
Like a rolling stone
Lola
Losing my religion
Luka
Madammen met een bontjas
Ma plantation
Mia
Meisjes
Man on the moon
Mr. Tambourine man
Mrs. Robinson
Mr. Jones
Ne me quitte pas
99 luftballons
N0 women, no cry
Non non, rien n'a changé
Oh Suzanne
Opzij opzij opzij
Ooit was ik een soldaat
Ona way
People are strange
Perfect day
Per spoor
Polly
Proud Mary
Paint it black
Redemption song
Quand les oisaux chantent
Ring ring, i've got to sing
Ring of fire
Rock around the clock
Rocking in a free world
Stand by me
Samsonrock
Satisfaction
Save tonight
Solitary man
She goes nanana
Son of a preacherman
Stairway to heaven
Sultans of swing
Streets of London
Suspicious minds
Suzanne
Sweet home Alabama
't Smidje
Sinds een dag of twee
Take a walk on the wild side
Time of your life
Tears in heaven
The boxer
Thank you for the music
The man who sold the world
There she goes
The passenger
The lion sleeps tonight
The wild rover
The times they are a-changing
Tomber la chemise
Under the bridge
Twee meisjes
Verdonken vlinder
Video killes the radio star
Vlaanderen boven
Wa are the world
We zullen doorgaan
We are the champions
Where is my mind?
What a wonderfull world
What's up
Where did you sleep last night?
Whiskey in the jar
Whit a little help from your friends
Who'll stop the rain
Yesterday
Wonderfull
You are my sunshine
Zo vrolijk
Nederlands
Bladmuziek
Keywords: liederen; bladmuziek